Species-Specific Gene, spt5, in the Qualitative and Quantitative Detection of Boletus reticulatus - Zhan Lei; Chen Zhang; Yinjiao Li; Lunzhao Yi; Ying Shang (Journal of Food Quality)
Boletus reticulatus is a wild edible fungus with high nutritional value in Yunnan Province. In this study, B. reticulatus was used as the research object to diagnose the species characteristics. A commercial kit was used to extract the DNA of various fungi, and the quality of DNA was determined by using universal fungus primers. Through sequence alignment, the spt5 gene was selected as the species-specific gene of B. reticulatus. This gene was then qualitatively and quantitatively analyzed by PCR. In the qualitative detection, the spt5 amplification products were only found in B. reticulatus which proved its good specificity. Meanwhile, SYBR Green I based quantitative PCR results were highly sensitive, and the limit of detection was 0.04 ng of genomic DNA. These experiments illustrated that spt5 is an ideal species-specific gene for the quantitative and qualitative detection of B. reticulatus. This method is also suitable for the analysis of the processed samples of B. reticulatus and the determination of the adulteration of edible wild mushrooms.